Pobreza energética y exclusión en Argentina: mercados rurales dispersos y el programa PERMER - Ibañez Martín, María María (2019)
This article analyzes the relationship between energy, poverty and social exclusion. Under this conceptual framework, the situation of the dispersed rural markets in Argentina and the Renewable Energies in Rural Markets Program (PERMER) as an inclusive and palliative policy of energy poverty are evaluated from the background and results review. It is concluded that the program has generated an advance in the access of traditionally excluded populations but that their results result in rural electrification, with limitations in their incidence in the inclusion and capacity development of thetarget population.